Using Geographic Information Systems (GIS) in Environmental Risk Analysis and Assessment: A Case Study on Baghdad City (Journal of Engineering, 2025)
Environmental quality for a healthy life is a major focus of scientific studies on human life and health. Rapid economic growth and urbanization have exposed major cities such as Baghdad to the risk of environmental problems, including desertification, air and water pollution, and high greenhouse gas emissions. These risks can be studied and assessed using Geographic Information Systems (GIS), which provide a comprehensive understanding of environmental issues and evidence-based remedies. Focusing on water and air pollution, this study will examine and assess environmental risks in Baghdad. The study identified areas with high concentrations of PM10, NO2, and SO2 through analyzing GIS maps. These areas are located in densely populated and traffic-intensive areas and are severely affected by pollution around major roads and industrial areas. Wind conditions and climate change also cause seasonal fluctuations in pollution levels. Although the Tigris and Euphrates rivers have suitable pH and nitrate levels, they contain significantly higher amounts of dissolved solids and phosphates, which may result from industrial and agricultural pollution. Land cover transformation results show an increase in the percentage of built-up area from 25% in 2016 to 45% in 2024, with a decrease in green areas from 40% to 30%. The average annual temperature increased from 21.5°C to 23.2°C, while rainfall decreased from 135 mm to 115 mm. PM₁₀ concentrations increased from 85 µg/m³ in 2018 to 110 µg/m³ in 2023, indicating a worsening of air pollution. The hotspot map shows higher concentrations near industrial areas and the Karkh–Doura corridor.